A longitudinal study of early childhood caries in 9- to 18-month-old Thai infants - Thitasomakul S, Thearmontree A, Piwat S, Chankanka O, Pithpornchaiyakul W, (Blackwell Synergy, 2006)
To examine the rate and pattern of early childhood caries (ECC) development and to investigate the transitional changes of the carious lesions during a follow-up period of 3–9 months